The Influence of Learning Models on Scientific Literacy in Physics Course: A Meta-Analysis Research - Yunika Apriyani; Yetti Supriyati; Gaguk Margono (International Journal of Science and Society, 2021)
This study aims to analyze the influence of learning models on students' scientific literacy skills. This research method is a meta-analysis with a sample of ten national and international journal articles. The results of this study indicate that the STEAM learning model, STEM, Problem Based Learning, Literacy Learning Model, E-learning, Project Based Learning or combination models have an influence on students' scientific literacy skills because they connect classroom learning activities with students' daily lives and motivate students to participate actively in the learning process.